Investigating adolescents’ online resilience: The role of parenting style, friendship quality, and social media self-efficacy - Ni Komang Yastri Anasuyari; Melly Latifah (Jurnal Psikologi Sosial, 2023)
In the digital era nowadays, social media has become a central part that cannot be separated from adolescents' daily lives. This can have a positive or negative impact, depending on adolescents' online resilience, namely the ability to survive in difficult, dangerous, and risky situations in the online world. This study aimed to analyze the influence of parenting style, friendship quality, and social media self-efficacy on adolescent online resilience. This study used an explanatory design located in Bogor City, West Java. This study involved 224 adolescents selected based on a purposive sampling technique, with the criteria being 15-18 years old, having complete parents and living together, and using social media. Data obtained through self-reporting using online questionnaires are then processed and analyzed using descriptive analysis and multiple linear regression tests on the SPSS 25.0 program. The majority of parents apply authoritative parenting styles predominantly. More than half of adolescents have the quality of friendship, social media self-efficacy, and online resilience in the moderate category. The results showed that the quality of friendship and social media self-efficacy significantly affected adolescent online resilience.